2017
DOI: 10.21595/jve.2017.17724
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical dynamic analysis for the cutting transmission system of the unmanned long-wall shearer under variable speed process

Abstract: The drum shearer is one of the main equipments of the long-wall mining system. A typical condition to adjust the hauling and drum speeds is when the drum load exceeds the allowable value due to the hardness increase of the coal seam. Two schemes are utilized in this condition herein: (1) increasing the drum speed directly and maintaining the hauling speed; (2) decreasing the hauling speed firstly, then increasing the drum speed, finally increasing the hauling speed to the original value. The electromechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Yi et al found that when the gear system resonates, the spectrograms of the current and electromagnetic torque obtain recognizable characteristics [5]. Liu et al proposed to include the calculation of all natural frequencies under different meshing conditions in the design of the transmission system, but to ignore the parameters of the meshing frequency and its frequency multiplication [6]. Jiang et al studied the electromechanical coupling torsional vibration characteristics of the gear transmission system driven by a low-speed and high-torque permanent magnet synchronous motor, and found that the electromagnetic effect reduces the first natural frequency of the system and inhibits the vibration of the gear [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Yi et al found that when the gear system resonates, the spectrograms of the current and electromagnetic torque obtain recognizable characteristics [5]. Liu et al proposed to include the calculation of all natural frequencies under different meshing conditions in the design of the transmission system, but to ignore the parameters of the meshing frequency and its frequency multiplication [6]. Jiang et al studied the electromechanical coupling torsional vibration characteristics of the gear transmission system driven by a low-speed and high-torque permanent magnet synchronous motor, and found that the electromagnetic effect reduces the first natural frequency of the system and inhibits the vibration of the gear [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Jia 11 , 12 established a coupled dynamics model of the transmission system of cutting part and the rocker arm shell based on an improved gear mechanics model, analyzed the dynamic response of the system under different loads, and obtained influence law of topology optimization of the shell on the characteristics of the gears. Liu 13 , 14 proposed a torsional dynamics modeling method for planetary gears, established the electro-mechanical coupling dynamics model for cutting part transmission system and obtained the dynamics response influence law of traction speed and drum load on that system via analysis method. Ge 15 established the electro-mechanical coupling dynamics model for the cutting unit transmission system, analyzed the dynamic characteristics of the system under impact load and proposed an active control strategy of motor torque compensation to suppress the dynamic loads caused by external loads with catastrophe characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Basing on improved gear mechanics model, Jia H. [11][12] established the coupling dynamics model for the transmission system of cutting part and the rocker arm shell, analyzed their dynamic response under different loads and obtained influence law of topology optimization of the shell on the characteristics of the gears. Liu C [13][14] proposed a torsional dynamics modeling method for planetary gears, established the electro-mechanical coupling dynamics model for cutting part transmission system of the shearer and obtained the dynamics response influence law of traction speed and drum load on that system via analysis method. Ge S. [15] established the electro-mechanical coupling dynamics model for the cutting unit transmission system, analyzed the dynamic characteristics of the system under impact load and proposed an active control strategy of motor torque compensation to suppress the dynamic loads caused by external loads with catastrophe characteristics.…”
Section: Introductionmentioning
confidence: 99%